Understanding Behavioral Intention in Implementation of the ICTs Based on UTAUT Model - Krismadinata, Krismadinata; Jalinus, Nizwardi; Pitra Rosmena, Hafeasi; yahfizham, yahfizham (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 10, No. 2 August 2019, 2019)
Innovation on Information Communication and Technology (ICT) are not suddenly accepted and directly used by individuals in work and workplace, even some individuals refuse to work using adoption ICTs. Therefore this research needs to be done to reveal what factors influence this attitude. This article aims to analysis variables or factors such as performance expectancy (PE) as X1, effort expectancy (EE) as X2, social influence (SI) as X3 and facilitating condition (FC) as X4 that contribute to the behavioral intention (BI) as Y of individual in accepted or rejected innovation based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model perspective. The method was applied factor analysis. A technique of collecting data using the checklist of questionnaire instrument, with total the population of 85 people, then according to tables of Isaac and Michael obtained the sample of 68 respondents who came from the Government Employees in the Disdikpora Dharmasraya Regency. The data were analyzed with the software tools of the Statistical Package for the Social Sciences (SPSS) version 22. The data collection time starts from November to December 2018. We found that X1, X2, X3, and X4 have significant effects on user acceptation based on UTAUT model.